Eurex-LUNa Abisko Trials Lawnmower Vectoring - Wehbe, Bilal; Hildebrandt, Marc; Creutz, Tom; Wirtz, Marius; Zipper, Michael (Zenodo, 2022)
Navigation data of the AUV DeepLeng during field trials in an ice-covered lake in Abisko, Sweden. For more information on this field trials: https://www.dfki.de/web/forschung/eurex-abisko This dataset is described in the paper M. Hildebrandt, T. Creutz, B. Wehbe, M. Wirtz and M. Zipper, "Under-Ice Field tests with an AUV in Abisko/Torneträsk," OCEANS 2022, Hampton Roads, Hampton Roads, VA, USA, 2022, pp. 1-7, doi:10.1109/OCEANS47191.2022.9977094. For more details on how to use the data files, please refer to the Readme.md Contact: tom.creutz@dfki.de, bilal.wehbe@dfki.de Funded by BMWi (Kennziffer 50 NA 2002)